Amish Christmas emergency - Lynn, Dana R. (Lynn, Dana R. Amish country justice., 2018)
Nurse Alexa Grant is hiding from her stalker in Amish country. When he finds her and starts making threats against her life, police officer Gavin Jackson must protect her.